Socio-economic and behavioural risk factors of visceral leishmaniasis in the East Champaran district of Bihar - Kumar, Navin; Singh, T. B.; Meena, L. P. (International Journal Of Community Medicine And Public Health, 2017)
Background: Visceral leishmaniasis is a chronic and potentially fatal parasitic disease of the viscera which affect the organs due to infection by Leishmania donovani. Visceral Leismaniasis, also known as Kala-Azar (KA) in the Indian subcontinent. The worldwide incidence is estimated to be between 146,700 and 282,800 cases per year. In India, it is endemic in the states Bihar and it contains more than 90 % of the cases of VL.In this region, Leishmania donovani is the only species causing VL. Objective: To find out the socio-economic and behavioural risk factors of VL in East Champaran district of Bihar. Methods: A case-control study was conducted to understand the socio-economic and behavioural risk factors associated with VL in areas of East Champaran district of Bihar, India. A total of 100 VL cases and 100 healthy controls selected randomly from the neighbourhoods of cases were included in the study. Results: The risk factors identified were showed that presence of a granary inside houses (P=0.000), sunlight inside the living room (P=0.000), banana trees near the houses (P=0.003), presence of domestic animal in the house (P=0.044), people sleep near the animal (P=0.000) and drainage system (P=0.000) were risk factors of VL. Conclusions: These results will be useful for further improvement in the VL control programs for intervention strategies in respect of separate granary house other than the living house, presence of sunlight inside the living rooms, banana trees far from the houses, separate domestic shelter for reducing transmission and incidence of this disease.